PENGARUH AMBANG BATAS PARLEMEN TERHADAP KEDUDUKAN PARTAI OPOSISI SERTA KAITANNYA DENGAN SISTEM PEMERINTAHAN PRESIDENSIL DI INDONESIA - Bernardinus Putra Benartin; Paulus Wisnu Yudoprakoso (Gloria Justitia, 2021)
With the amendment to the 1945 Constitution of the Republic of Indonesia, Indonesia adopts a presidential system of government, this is reinforced by the existence of articles that strengthen the president as head of state and head of government. Therefore, the government or in this case the president has a bigger power room. To realize an effective democratic system, it is necessary to have government opposition in parliament as a form of people's representation, which is necessary to provide criticism, alternative policies and control of power. However, to achieve proportionality between the government coalition parties, apart from improving the internal parties involved in the general elections, the quality of the general election system contained in the law must also be improved. There must a significant increase in the percentage threshold that eliminates the votes of small and medium-sized parties that eliminate valid votes from the general election, thereby reducing the probability of realizing the proportionality of parties with coalitions of government and opposition parties in parliament.